Analisis Determinan Sektor Pertanian dan Sub Sektor Unggulan di Kabupaten Muaro Jambi - Nofridianti, Aulia; Junaidi, Junaidi; Safri, Muhammad (Universitas Batanghari Jambi, 2024)
This research aims to determine the contribution of the agricultural sector to the GRDP of Muaro Jambi Regency, to determine and analyze what factors influence the growth of GRDP in the agricultural sector in Muaro Jambi Regency, and to determine and analyze the leading agricultural sector in Muaro Jambi Regency. Analysis year 2002-2022. The analytical method used is quantitative descriptive analysis and qualitative analysis. The results of the research show that the economic growth of Muaro Jambi Regency in 2002-2022 is 39.38%, the factors that influence the growth of GRDP in the agricultural sector in Muaro Jambi Regency are the area of agricultural land and investment in the agricultural sector, while the workforce in the agricultural sector and agricultural production are not has a significant effect on the growth of GRDP in the agricultural sector in Muaro Jambi Regency. The leading agricultural sector in Muaro Jambi Regency, as a result of location quotient analysis, is that there are 8 economic sectors classified as basic sectors and 9 non-basic sectors. The results of the dynamic location quatient analysis show that there are 8 economic sectors that have prospective potential and there are 9 economic sectors that do not have prospective potential. The results of the classic shift share analysis show that Jambi Province influences the increase in GDP of Muaro Jambi Regency, the highest economic shift value is in the primary sector, the second secondary sector and the third tertiary sector.